Modeling the Effects of Hydrodynamics on Thermal Stratification and Algal Blooms in the Xiangxi Bay of Three Gorges Reservoir - Xu, Hui; Yan, Meng; Long, Lianghong; Ma, Jun; Ji, Daobin; Liu, Defu; Yang, Zhengjian (Frontiers in Ecology and Evolution, 2021)
Algal blooms have been reported in some tributary bays since the initial impoundment of Three Gorges Reservoir, which has seriously affected the water ecology and drinking water safety. Hydrodynamics plays a crucial role in algae growth. The recent numerical models of hydrodynamics and water quality are effective to identify the effects of hydrodynamics on phytoplankton and find potential strategies for controlling algal blooms. In this study, the CE-QUAL-W2 model was applied to simulate the hydrodynamics and algal blooms in the Xiangxi Bay (XXB) of the Three Gorges Reservoir. The model performed well in simulating flow patterns, water temperature profile, and algal blooms. The results indicated that the hydrodynamics showed the spatial and temporal differences in the XXB. In the mouth area, the intensity and plunge depth of density currents were dynamic and characterized by a typical seasonal pattern. The transformation of density currents from interflow to overflow will provide more opportunities for vertical mixing, resulting in un-stratification and reducing of algal blooms. However, in the middle and upper areas, strong stratification and low velocity at upstream provide enough favorable conditions for the growth of algae and increase algal blooms. The simulation results revealed that the variation of mixing depth explains the spatial and temporal differences of Chl.a. It played a vital role in seasonal stratification and the dynamics of phytoplankton succession in XXB.